Diagnosis and management of chronic cough: similarities and differences between children and adults - Weinberger, Miles (F1000Res, 2020)
Cough is a natural process that protects the airway. Cough can occur spontaneously or voluntarily. It is considered chronic when it is present for longer than 4 weeks in children or 8 weeks in adults. In both, chronic cough causes patient distress and increased healthcare utilization. Etiologies of pediatric chronic cough include asthma, protracted bacterial bronchitis, tracheomalacia, habit cough, and various systemic disorders. While some diagnoses are identifiable by careful history alone, others require testing guided by specific pointers. Flexible fiberoptic bronchoscopy has been an important tool to identify etiologies of chronic cough that were not otherwise apparent. In adults, asthma and bronchitis are well-defined etiologies of chronic cough, but much chronic cough in adults is largely a conundrum. Reviews of adult chronic cough report that at least 40% of adults with chronic cough have no medical explanation. Gastroesophageal reflux and upper airway cough syndrome (a.k.a. post-nasal drip) have been common diagnoses of chronic cough, but those diagnoses have no support from controlled clinical trials and have been subjected to multiple published critiques. Cough hypersensitivity is considered to be an explanation for chronic cough in adults who have no other confirmed diagnosis. Gabapentin, a neuromodulator, has been associated with a modest effect in adults, as has speech pathology. While habit cough has not generally been a diagnosis in adults, there is evidence for a behavioral component in adults with chronic cough. Treatment for a specific diagnosis provides a better outcome than trials of cough suppression in the absence of a specific diagnosis. More data are needed for chronic cough in adults to examine the hypothesized cough hypersensitivity and behavioral management. This article reviews etiologies and the treatment of chronic cough in children and the conundrum of diagnosing and treating chronic cough in adults.